Using chatbots to teach STEM related research concepts to high school students - Ureta, Jennifer C. (Animo Repository, 2018)
Research or capstone subject is not in the curriculum of ICT strand, but it is only offered in the Academic track. However, given the current technology trends, it can be deduced that research is also essential to help the students become active and creative professionals in their respective fields in the future. In this paper, we present the use of chatbots for teaching research concepts to senior high school students. The students were tasked to create chatbots for the different domains that they were interested in through the use of Dialogflow. This paper also discusses the teaching methodology that was used to deliver the course. © 2018 Asia-Pacific Society for Computers in Education..All Rights Reserved.